2014
DOI: 10.1111/cid.12230
|View full text |Cite
|
Sign up to set email alerts
|

An Accuracy Study of Computer‐Planned Implant Placement in the Augmented Maxilla Using Mucosa‐Supported Surgical Templates

Abstract: Computer-aided implant planning showed to be a clinically relevant tool. However, this study emphasizes that the surgeon should take into account that deviations are larger compared with implant placement without augmentation procedure. Deviations are mainly caused by angulations and translations of the surgical template.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 39 publications
5
39
1
2
Order By: Relevance
“…Controversially, Verhamme et al. () stated that the use of fixation pins could preclude the surgeon to check continuously the implant preparation site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversially, Verhamme et al. () stated that the use of fixation pins could preclude the surgeon to check continuously the implant preparation site.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors recommended the use of these tools to reduce the deviation in the final position of the implant and to increase the stability of the SLA template (Arisan et al 2010b;Cassetta et al 2011Cassetta et al , 2013bD'haese et al 2012;Di Giacomo et al 2012). Controversially, Verhamme et al (2014) stated that the use of fixation pins could preclude the surgeon to check continuously the implant preparation site.…”
Section: Summary Of the Main Findingsmentioning
confidence: 99%
“…A precise implant site can reduce the stress concentration and provide an esthetic outcome for restorative dentist. In recently guide surgery studies, the mean angle deviation between the planned and placed implants is from 2.48°to 6.53°. Compared with other advocated techniques, the results of the preliminary in vivo test satisfied the clinical appearance requirements.…”
Section: Discussionmentioning
confidence: 99%
“…25 A precise implant site can reduce the stress concentration and provide an esthetic outcome for restorative dentist. In recently guide surgery studies, [26][27][28] the mean angle deviation between the planned and placed tooth can be manually separated from radiographic guide and reduced probability of manually error after radiographic guide conversion. This study used both GCM and SLA method to obtain the surgical guide.…”
Section: In Vivo Testmentioning
confidence: 99%
“…Previously performed implant validation studies have shown that implant deviations between the planned and postoperative implant position are influenced by angulations and translations of the surgical template. 1 The aim of this study was to develop a surgical template that guarantees no mismatch between the planned implant position and that achieved.…”
mentioning
confidence: 99%